Erosimetria a quente: equipamento, adequações e correlações dos valores obtidos com as propriedades de concretos refratários - Gonçalves, Lidia Regina Garcia (2011)
The erosion wear is a mechanism that results in the removal of material from the surface by erosive particles. In some applications, such as calciners used in the aluminum industry and risers of the petrochemical industry, the erosive wear is one of the most critical problems of the refractory lining. Since they are equipments used in the critical phases of these industries production process, needs of long maintenance stops can severely impact their productive process, resulting in significant financial losses. Aiming to maximize the periods in which maintenance calls are not required, refractory materials qualifications are periodically performed in order to help on selecting the highest performance materials. However, even though the service temperatures for these applications are usually high, nowadays the erosion tests are performed only at room temperature in these qualification processes. Additionally, it uses a correlation that assumes that a higher hot modulus of rupture will result in a higher erosive resistance, in the same temperature range. Thus, aiming to reproduce the operation conditions in a more realistic way, the main goal for the present work (which was conducted in partnership with Alcoa and Petrobras) was to enhance the operation of the hot erosion equipment previously developed by other members of GEMM/UFSCar (Materials Microstructure Engineering Group), by making adjustments on its initial design. This enhancement resulted in the development of a calibration methodology for the equipment and the elaboration of a standard procedure for hot erosion tests. And finally, refractory materials were characterized and the results indicated that, for the analyzed materials, the erosive behavior varies as function of the temperature and that there is not always a linear correlation between erosion resistance and the other properties analyzed.